La santidad barroca en la pintura mural del Carmen Alto de Quito. Iconografía e iconología (Debates) - Herrera González, Esteban (2021)
The article considers the influence of the Council of Trent and Jesuit philosophy on the formulation of the concept of saintliness and its representation in a series of murals of Quito’s Carmelo de San José, inspired by a series of prints from Flanders. It also examines the iconological type, to ascertain the underlying reasons for building these sanctuaries and how their iconographic messages, subscribing to an ideology arising from the Counter-Reformation, exerted an impact on events occurring in the Audiencia de Quito in the eighteenth century.